(untitled) (Repertorio Científico, 2023)
The objective of this study is to explain the performance of a knowledge network, understood as a management, production and transfer system between the demands of the environment and the capabilities of the organization. A non-experimental, cross-sectional and correlational study was carried out with a non-probabilistic sample selection of 100 administrators, teachers and students of a public university, considering their interaction in professional practices. The results show a confirmatory structure of three components related to the formation, production and transfer of knowledge, although the relationship matrix suggests the inclusion of another factor alluding to the creation of knowledge observed in creative organizations. The contrast of the model in another sample and study context is recommended, as well as the adjustment of the dimensions to a model with the inclusion of a fourth factor.